OPTIMIZATION OF JAMBLANG (Syzygium Cumini (L.) Skeels) FRUIT EXTRACT LEVELS IN YOGHURT FORMULATION AS ANTIOXIDANT - Yanuarto, Tri; Nurkhasanah; Hayu Nurani, Laela (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
The reactivity of oxidant compounds that exceed the limits of antioxidant protection ability can cause chain reactions which cause interference with the system. Prevention is needed to neutralize the oxidants, so that exogenous antioxidants are needed. One example is the jamblang fruit (Syzygium cumini (L)) which has high antioxidant activity due to its natural anthocyanin. The purpose of this study was to determine the optimal form of yogurt with the addition of jamblang fruit extract with a concentration of 0%, 5%, 7.5% and 10% and the quality of SNI. Tests carried out include physical, chemical and microbiological tests, namely sensory, acid content, total protein, fat content, and a number of bacterial starters, as well as safety tests with storage at 4° C then 0, to 7, 14th, 21st and 28th day. Data analysis using MANOVA. The results of the effect of the product showed that the fruit of yogurt with 10% extract level provided good stability during storage. Decreased antioxidant levels on day 7 to day 28. Antioxidant activity is more stable than antioxidant jamblang fruit extract. The antioxidant activity of yogurt with 5% jamblang fruit extract; 7.5% and 10% on day 0% % inhibition value of 57.48%; 62.06%; and 73.01%.